The Dichloromethane Fraction of Croton sonorae, A Plant Used in Sonoran Traditional Medicine, Affect Entamoeba histolytica Erythrophagocytosis and Gene Expression - Villegas-Gómez, Isaac; Silva-Olivares, Angélica; Robles-Zepeda, Ramón Enrique; Gálvez-Ruiz, Juan-Carlos; Shibayama, Mineko; Valenzuela, Olivia (Frontiers in Cellular and Infection Microbiology, 2021)
Intestinal parasites are a global problem, mainly in developing countries. Obtaining information about plants and compounds that can combat gastrointestinal disorders and gastrointestinal symptoms is a fundamental first step in designing new treatment strategies. In this study, we analyzed the antiamoebic activity of the aerial part of Croton sonorae. The dichloromethane fraction of C. sonorae (CsDCMfx) contained flavonoids, terpenes, alkaloids, and glycosides. The ultrastructural morphology of the amoebae treated for 72 h with CsDCMfx was completely abnormal. CsDCMfx reduced erythrophagocytosis of trophozoites and the expression of genes involved in erythrocyte adhesion (gal/galnac lectin) and actin cytoskeleton rearrangement in the phagocytosis pathway (rho1 gtpase and formin1). Interestingly, CsDCMfx decreased the expression of genes involved in Entamoeba histolytica trophozoite pathogenesis, such as cysteine proteases (cp1, cp4, and cp5), sod, pfor, and enolase. These results showed that C. sonorae is a potential source of antiamoebic compounds